Collecting development data with mobile phones: Key considerations from a review of the evidence - Chesterman, Sabrina; Lamanna, Christine; Kalamatianou, Sofia; Rosenstock, Todd S. (2017)
Growth in mobile phone access and ownership presents an opportunity to collect more data, more frequently, from more people, and for less money. There are multiple ways to collect data with mobile phones (SMS, voice calls, etc.), each with particular strengths and weaknesses. n The best mode of data collection depends on the characteristics of the target population (e.g. literacy, network access, acceptability of using mobile phones, etc.) and of the data to be collected (e.g. quantitative vs. qualitative, number of questions, sensitivity of information, etc).